2021
DOI: 10.3390/agriculture11030202
|View full text |Cite
|
Sign up to set email alerts
|

Agribusiness as an Attractive Place to Work––A Gender Perspective

Abstract: Agribusiness is both a complex social process and a market structure, consisting of many independent economic entities that generate demand for labour in the sector. The role of people whose activity is directly or indirectly related to the production of food products, the acquisition of resources, and the processing and production of ready food was considered. The way gender affects people’s decision to work in this sector and university graduates’ perception of agribusiness being an ideal job were also analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Additionally, the existing literature has not been much interested in whether the measurement of job attributes is accurate and comparable in different cultural contexts [8,19]. For example, research dedicated to agricultural businesses found out that women prefer the opportunity for self-development and good social relations, while for men, it is economic benefits and job-related prestige driving their job attitudes [20]. In international research analyzing the most important determinants of job attributes, we assume these concepts and scales are understood in the same way but in different contexts.…”
Section: Measurement and Classification Of Job Attributes: A Literatu...mentioning
confidence: 99%
“…Additionally, the existing literature has not been much interested in whether the measurement of job attributes is accurate and comparable in different cultural contexts [8,19]. For example, research dedicated to agricultural businesses found out that women prefer the opportunity for self-development and good social relations, while for men, it is economic benefits and job-related prestige driving their job attitudes [20]. In international research analyzing the most important determinants of job attributes, we assume these concepts and scales are understood in the same way but in different contexts.…”
Section: Measurement and Classification Of Job Attributes: A Literatu...mentioning
confidence: 99%
“…Shortages of workers on each stage of supply chains cause bottlenecks in primary animal production, processing and meat distribution. The meat industry in developed countries experienced staffing problems before COVID-19 [92,93]. The pandemic aggravated the recruitment difficulties in the group of skilled workers and deepened the need for overseas workers.…”
Section: Implications Of the Difficulties In Marinating The Resilience On The Analyzed Meat Marketsmentioning
confidence: 99%
“…Youth involvement and advancement in agribusiness were hampered by restricted access to land, inadequate financial services, gender or sex, outdated agricultural technology, and attitudinal problems. The function of it was regarded as those whose activity is directly or indirectly associated with the production of food items, the acquisition of resources, and the processing and manufacture of ready food (Kozera-Kowalska & Uglis, 2021). In Africa, although the agri-food sector has a vast potential to offer attractive employment opportunities for burgeoning youth, a negative perception of agriculture persists among them (Mkong, Abdoulaye, Dontsop-Nguezet, Bamba, Manyong & Shu, 2021).…”
Section: Introductionmentioning
confidence: 99%